Assessing the distribution of mayflies (Ephemeroptera: Insecta) in the Brazilian Amazon to guide more effective conservation. Issue 4 (17th March 2023) - Cardoso, Mylena Neves; Shimano, Yulie; Cruz, Paulo Vilela; Boldrini, Rafael; Mariano, Rodolfo; Nessimian, Jorge Luiz; Molineri, Carlos; Salles, Frederico Falcão; de Andrade, André Felipe Alves; De Marco, Paulo; Juen, Leandro
Abstract: Environmental changes are increasingly frequent, resulting in adverse impacts on biodiversity. These effects are more harmful when superimposed on areas of high biodiversity such as the Amazon region, in which the gaps in knowledge of the number of existing species and how they are distributed. This article reviews the known geographical distributions of Ephemeroptera in the Brazilian Amazon based on the current uneven sampling effort to identify which species and biodiversity hotspots are poorly protected, and where more work is required to address the conservation needs of this group. A sampling effort index was created to identify which areas have the highest potential mayfly richness and the greatest concentration of knowledge gaps. The mayfly records were combined with environmental variables to generate predictive models of the areas suitable for mayflies using species distribution modelling, and species that lack protection in conservation units and indigenous territories were indicated as priorities for future inventories. Caenis pflugfelderi, Microphlebia surinamensis, Tricorythopsis pseudogibbus and Tricorythodes sp. nov. were identified as threatened in the Brazilian Amazon given that they were recorded in an unprotected area of intense land use with a restricted potential distribution. Mayflies have been recorded in only 5% of the Brazilian Amazon biome. The model indicated a greater diversity in the northern and north‐eastern Amazon. The sampling effort index indicated a total area of 46, 225 km 2 in mayfly biodiversity not protected by conservation units or indigenous territories. This study raises awareness of the importance of intensifying studies of Ephemeroptera in the Brazilian Amazon, and demonstrates that the conservation units or indigenous territories do not protect many species.